Digital Literacy on SME Business Performance and The Mediating Role of Entrepreneurial Skills - Intan Novela Q.A; Hunik Sri Runing Sawitri; Asri Laksmi Riani; Suryandari Istiqomah; Anastasia Riani Suprapti; Mugi Harsono (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: In the digital era, SMEs must adapt to technological advancements to remain competitive. Digital literacy is increasingly recognized as a crucial factor in enhancing entrepreneurial skills and business performance. Purpose: The aim is to uncover how improving digital literacy can lead to better business outcomes for SMEs. Design/methodology/approach: The research targeted 101 SMEs from manufacturing and trade sectors in the Greater Solo area. Data were collected through online surveys and offline methods. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was used to test the hypotheses.Findings/Result: The study found that digital literacy positively affects the development of entrepreneurial skills, which in turn enhances business performance. Performance was measured through revenue growth, profitability, market share, and customer satisfaction. Digital literacy is a key driver of entrepreneurial skills development and improved business performance in SMEs. Investing in digital literacy can significantly enhance SMEs' competitive edge and overall success.Conclusion: The research concludes that digital technology is vital for improving SMEs' performance and competitiveness by expanding market access, attracting customers, and increasing sales. Additionally, digital literacy is crucial for enhancing operational efficiency, product and service innovation, and customer communication.Originality/value (State of the art): The research broadens the understanding of digital literacy, positioning it as more than just a technical skill. It shows that digital literacy equips SMEs with essential tools for market access, operational efficiency, innovation, and customer communication. By linking digital literacy to strategic business study highlights its critical importance in navigating the modern digital economy. Keywords: digital literacy, entrepreneurial skills, business performance, SMEs, digital era